Treatability of vegetable oil industry effluents through physical-chemical methods - Saatci, Y; Hasar, H; Cici, M (Inst Lebensmitteltechnologie Analytische Chemie, 2001)
In this study, a vegetable oil factory (Karadeniz Birlik Dogan Erdil) was selected as representative of this sector and its production method evaluated and its effluent investigated. During the first part of the test program, quality of the raw effluent was determined. Alternatives of possible physical-chemical treatment were examined by using pilot scale and laboratory models. The most efficient treatment combination has been determined under the objective of this study. The results showed that 17.65 - 69.12 % of COD and 28.50 - 76.32 % oil-grease were removed by using Dissolved Air Flotation (DAF), 63.19 - 80.66 % COD and 76.95 - 83.38 % of oil-grease removed in the acid cracking and coagulation with lime, 88.14 - 92.99 % of COD and 69.89 - 92.11 % oil-grease removed by using alum, and 94.66 - 96.25 % of COD and 93.81 - 96.16 % of oil-grease removed by using ferric chloride for treatment of the same wastewater. The treatment efficiency of coagulation by alum process was raised up to the range of 94.66 - 95.37 % of COD and 96.88 - 97.78 % of oil-grease by using alum-clay process.
Keywords: vegetable oil industry; Dissolved Air Flotation (DAF); coagulation; acid cracking